Signals of new physics at the LHC and colliders of future generation - Navarro, Roy Daniel Alva (2016)
Searches for new physics beyond the Standard Model are important subjects at the current Run-2 of the Large Hadron Collider (LHC) and next generation colliders. In this context, we make independent studies of the phenomenology of a new hypothetical heavy Majorana neutrino (N) and a heavy spin-1 charged vector (W¿) at the LHC and a future 100 TeV very large hadron collider (VLHC), we also study the potential of the future International Linear Collider (ILC) to measure the rare h ! Z Higgs decay. Toward this end, the N production via the W fusion process is investigated and found it to be larger than the Drell-Yan production for mN > 1 TeV at the 14 TeV LHC and for mN > 770 GeV at the 100 TeV VLHC. Then we computed the discovery potential of the these colliders to discover an N using the same-sign dimuon channel. In the case of the h ! Z Higgs decay we investigated the Higgsstrahlung production at the 250 GeV ILC, we found that a sensitivity of 58% can be reached in the inclusive ¿?¿ X channel with 3 ab.1, where X denotes the inclusive decay of the Z boson from the Higgs. Finally, in the case of the WW, we studied its contribution to the h ! Higgs decay process and constrained the strength of the WWWWh interaction. Finally, we study the Drell-Yan WW production with its decay to the Wh pair at the LHC.